[Aerial view of Cal Poly] (1973)
View of San Luis Obispo and Cal Poly campus, California Boulevard, Highway 1, Mott Gym, Yosemite, Sierra Madre, red-brick dorms, North Mountain, Engineering East, Engineering West, Agricultural Engineering - looking northwest